Innovation of touch projector technology and its purpose - Alyami, Mona Majed; Mohamad Ali, Noor Azian (IJSER, 2015)
The primary objective of this article is to explain about touch projector technology concept and how to use it. This paper intention is to look at the present touch projector as a new technology aimed to enable performing tasks as a huge touch screen. This paper briefs on the historical background and provide review of three recent devices which are TouchPico, Cicret Bracelet and Dell Interactive Projector S520. The discussion focuses on their uses in business, education and entertainment. Additionally some areas of improvements are highlighted such as the return value and surface problems. Finally, this paper offer some suggestions to make the devices better.